Genes enterotoxigênicos e resistência à meticilina em Staphylococcus aureus isolados de leite caprino - Rebouças, Germana Guimarães (Universidade Federal Rural do Semi-Árido, 2015)
The aim of this study was to investigate the presence of enterotoxigenic and methicillin-resistant genes in Staphylococcus aureus isolated from goat milk obtained from Rio Grande do Norte state producers. To achieve such goal, 49 samples of goat milk and searched for S. aureus. The colonies were isolated in Petrifilm plates, Staph Express 3M model and biochemically identified. Afterwards, the isolated strains underwent an assessment to evaluate their antibiotic resistance profile, through the use of disk diffusion technique on Mueller-Hinton agar. Following we carried out a polymerase chain reaction (PCR) to search for the following selected genes: 16S rRNA (for molecular identification of S. aureus), mecA (characterizes the methicillin-resistant S.aureus) and enterotoxigenic genes (sea, seb-sec, sec, sed, see, seg, seh, sei, sej and tsst-1). Results from morphological and biochemical analyses revealed that all isolated strains belonged to the Staphylococcus aureus species. We also observed, through the antibiogram, high percentage of resistance to the antibiotics penicillin G (87.75%) and oxacillin (75.51%). Multidrug resistance was detected in 73.46% of the isolated strains. Analyzing the PCR, we confirmed that 100% of the isolated strains were S. aureus because of the amplification of the 16S rRNA gene. The mecA gene was found in 4.08% of the samples. In samples confirmed as S. aureus, concerning the research for staphylococcal enterotoxins (SE), there was amplification of the sej gene fragments in 79.5% of the samples, followed by the sei gene in 48.9%, sed gene in 22.4%, sea gene in 12, 2%, seh and sec genes in 8.1%, and sec gene in 2% for the samples. We did not observe any amplification for the seb-sec, see and tsst-1 genes. The strains of S. aureus isolated from goat milk have shown the presence of genes responsible for the production of toxins, a fact that requires greater care when processing this milk in the dairy industry. In addition, to antibiotic resistance and detection of mecA gene also leads to concern, can pose risks to consumer health
Enterotoxigenic genes and resistance to methicillin in Staphylococcus aureus isolated from goat milk
Keywords: Milk processing; Milk - Microbiological quality; Staphylococcal enterotoxin; PCR; Processamento de leite; Leite - qualidade microbiológica; Enterotoxinas estafilocócicas; PCR; CIENCIAS AGRARIAS::MEDICINA VETERINARIA